Transformasi Sosial di Era Digital dan Implikasinya pada Masyarakat Zaman Now (Suatu Kajian Dalam Perspektif Sosiologi Digital) - Mua, Marianus Muharli; Heatubun, Antonius (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2024)
This study examines social transformation in the digital era and its implications for contemporary society from the perspective of digital sociology. The research explores how technological changes are altering communication patterns, social interactions, economic structures, and other aspects of modern life. The analysis covers shifts in consumption patterns, employment, culture, identity, and political participation, while also highlighting the emergence of digital inequality. Despite the benefits of such transformations, such as broader access to information and greater political engagement, there are significant challenges, including disparities in technology access and digital skills, as well as the risks associated with irresponsible use of technology. Addressing these challenges requires cross-sector collaboration. Enhancing technology accessibility and skills, promoting digital inclusivity, and managing the social and economic impacts of technology are crucial for creating a sustainable and inclusive society in this digital age. With appropriate awareness and prudent actions, we can leverage the positive potential of technological changes to improve collective well-being and advance society towards a better future.